(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background:Atopic dermatitis is a chronic inflammation of skin disease that is characterized by recurrent acute pruritus and dry skin. Mostly, atopic dermatitis is predominant in young children. The problems of increasing prevalence and high impact of disease on quality of patients and family’s life, necessities identifying many atopic dermatitis prevention planes. Objective:To determine the effect of Artemisia annua flavonoids fraction in comparison with tacrolimus in atopic dermatitis like mice model. Methods:This study is a prospective, randomized, placebo and controlled animal designed. Thirty-two male Albino mice that six weeks age included in this study. The mice were randomly divided into four groups. Group I without treatment (Healthy). Group II only inducer, phthalic anhydride used. Groups II, III, and IV subjected to phthalic anhydride solution, which was applied on the dorsum of the back skin at 9 A.M. three times a week for four weeks. After three hours of phthalic anhydride application, treatment is used for group III (Tacrolimus 0.03% ointment), and group IV (flavonoids fraction 1.2 mg /kg ointment) topically once daily at 12 P.M. for three times a week for four weeks). Serum IgE and immunohistochemistry of skin tissue IL-4 score, and IL-13 score were measured. Results:High significant decrease in immunohistochemistry of skin tissue IL-4, and IL-13 in flavonoid fraction group were found. Conclusion:The flavonoid fraction has an effect on the skin immunohistochemistry parameters and probably on atopic dermatitis like mice model. Keywords:Atopic dermatitis, Artemisia annua, flavonoids Citation:Hameed MF, Abu-Raghif AR, Kadhim EJ. Effect of topical flavonoid fraction from Artemisia annua in comparison with tacrolimus on induced atopic dermatitis in mice. Iraqi JMS. 2019; 17(3&4): 231-237. doi: 10.22578/IJMS.17.3&4.10